KRIMINALISASI PROFESI DOKTER - Novi Kristanti, Felizia; Purwanti, Ni Putu (Kertha Wicara : Journal Ilmu Hukum, 2015)
The notion of medical malpractice has commonly occurred among doctors nowadays. Severalcase reports by patient, mostly resulting to criminal penalty and brought some controversiesamong society. This notable medical profession carries great responsibilities, which seemsutterly unfair to be condemned such penalty in case of unpredictable yet unfortunate outcomewhile on the other hand, patients have their own rights for justice itself. There are severalconditions which might harm doctors to be discussed through this writing since doctors andpatients are legally related. The research method of this paper is normative research methodcause of void of legal norms on Laws and Regulation Number 29 Year 2004 concerningMedical Practice. Based on Chapter X Laws and Regulation Number 29 Year 2004concerning Medical Practice, doctors are sentenced criminal verdict in matters legally due toadministrative problem such as non-possession of registration number. Based on an analysis,doctors are to be criminalized upon certain condition which are violation against the law,errors during practice, capability of being responsible, and the absence of underlyingexcuses to undo the penalty. It is expected for doctors to work carefully, attentively,benevolently to avoid or at least minimize error. More importantly, a harmonious rapportand mutual respect for rights and obligations between both parties is also expected tohappen.
Keywords: Legal responsibility, Criminalization, Doctor, Patient